Pengaruh Model Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, and Review) terhadap Kemampuan Menganalisis Unsur Naskah Drama Siswa Kelas XI SMA Negeri 3 Lubuklinggau - Sartika, Wila; Effendi, M. Syahrun (UNIB Press, 2019)
The purpose of this study was to determine the effect of the PQ4R model (Preview, Question, Read, Reflect, Recite, and Review) on the ability to analyze the drama script elements of class XI students of SMA Negeri 3 Lubuklinggau. This research method is an experimental method. The population of class XI students is 258 students consisting of 8 classes. The sampling technique uses simple random sampling technique and the research sample is class XI IPA 1 totaling 30 students and class XI IPA 2 totaling 30 students. Data collection using test techniques. Data were analyzed using the